Kv7 Channels in Lung Diseases - Mondejar-Parreño, Gema; Perez-Vizcaino, Francisco; Cogolludo, Angel (Frontiers in Physiology, 2020)
Lung diseases constitute a global health concern causing disability. According to WHO in 2016, respiratory diseases accounted for 24% of world population mortality, the second cause of death after cardiovascular diseases. The Kv7 channels family is a group of voltage-dependent K+ channels (Kv) encoded by KCNQ genes that are involved in various physiological functions in numerous cell types, especially, cardiac myocytes, smooth muscle cells, neurons and epithelial cells. Kv7 channel α-subunits are regulated by KCNE(1-5) ancillary β-subunits, which modulate several characteristics of Kv7 channels such as biophysical properties, cell-location, channel trafficking and pharmacological sensitivity. Kv7 channels are mainly expressed in two large groups of lung tissues: pulmonary arteries (PA) and bronchial tubes. In PA, Kv7 channels are expressed in smooth muscle cells (PASMC); while in the airway (trachea, bronchus and bronchioles), Kv7 channels are expressed in airway smooth muscle cells (ASMC), epithelial cells (AEP) and vagal airway C-fibers (VACF). The functional role of Kv7 channels may vary depending on the cell type. Several studies have demonstrated that the impairment of Kv7 channel has a strong impact on pulmonary physiology contributing to the pathophysiology of different respiratory diseases such as cystic fibrosis, asthma, chronic obstructive pulmonary disease, chronic coughing, lung cancer and pulmonary hypertension. Kv7 channels are now recognized as playing relevant physiological roles in many tissues, which has encouraged the search for Kv7 channel modulators with potential therapeutic use in many diseases including those affecting the lung. Modulation of Kv7 channels has been proposed to provide beneficial effects in a number of lung conditions. Therefore, Kv7 channel openers/enhancers or drugs acting partly through these channels have been proposed as bronchodilators, expectorants, antitussives, chemotherapeutics and pulmonary vasodilators